2014
DOI: 10.3389/fnana.2014.00114
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal MHC-I expression and its implications in synaptic function, axonal regeneration and Parkinson’s and other brain diseases

Abstract: Neuronal expression of major histocompatibility complex I (MHC-I) has been implicated in developmental synaptic plasticity and axonal regeneration in the central nervous system (CNS), but recent findings demonstrate that constitutive neuronal MHC-I can also be involved in neurodegenerative diseases by playing a neuroinflammtory role. Recent reports demonstrate its expression in vitro and in human postmortem samples and support a role in neurodegeneration involving proinflammatory cytokines, activated microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 81 publications
2
87
0
Order By: Relevance
“…Evidence also suggests that MHC I is involved with synaptic pruning during cortical development12, 13, 14, 16, 17, 18, 19, 20, 21 and following injury22, 23, 24, 25 and contributes to neuronal plasticity 16, 17, 26, 27. These findings also suggest that retrogradely induced MHC class I may contribute to the diffuse synaptopathy observed in MS and other neurodegenerative diseases 28, 29, 30, 31, 32, 33, 34, 35. However, whether human neurons and axons respond to inflammatory stress in this way is unknown, and the dearth of methods for efficiently culturing human neurons and isolated axons has prevented robust analysis.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Evidence also suggests that MHC I is involved with synaptic pruning during cortical development12, 13, 14, 16, 17, 18, 19, 20, 21 and following injury22, 23, 24, 25 and contributes to neuronal plasticity 16, 17, 26, 27. These findings also suggest that retrogradely induced MHC class I may contribute to the diffuse synaptopathy observed in MS and other neurodegenerative diseases 28, 29, 30, 31, 32, 33, 34, 35. However, whether human neurons and axons respond to inflammatory stress in this way is unknown, and the dearth of methods for efficiently culturing human neurons and isolated axons has prevented robust analysis.…”
Section: Introductionmentioning
confidence: 73%
“…16,17,26,27 These findings also suggest that retrogradely induced MHC class I may contribute to the diffuse synaptopathy observed in MS and other neurodegenerative diseases. [28][29][30][31][32][33][34][35] However, whether human neurons and axons respond to inflammatory stress in this way is unknown, and the dearth of methods for efficiently culturing human neurons and isolated axons has prevented robust analysis. Indeed, the study of human CNS axon biology in general is hindered by the technical challenges of generating isolated fields of patientspecific axons.…”
Section: Introductionmentioning
confidence: 99%
“…Localization of MHC mRNA in various brain regions suggests to be involved in the early neurodevelopment (Linda et al, 1999;Huh et al, 2000). Neural MHC expression is considered to play a role in early developmental synaptic plasticity (Cebrián et al, 2014a(Cebrián et al, , 2014bElmer andMcAllister, 2012, Shatz, 2009). Further, Cebrián et al (2014aCebrián et al ( , 2014b demonstrated that MHC I molecules are expressed by substantia nigra dopaminergic and locus coeruleus neurons in human postmortem samples of adult controls and Parkinson's disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cpg15 has been shown to be an important regulator of synapse formation and dendritic complexity and is required during the critical period for normal OD plasticity (Picard et al, 2014). Conversely, MHCI negatively regulates synapse development and deletion of MHCI or PirB, a MHCI receptor, enhances visual system plasticity in vivo (Cebrian et al, 2014;Shatz, 2009). Although the exact contribution of subtle changes in excitatory synapse density to visual circuit function in general and OD plasticity in particular is not well understood, Hofer et al, demonstrated that spine formation and turnover is dramatically affected by MD in layer 5 cortical neurons (Hofer et al, 2009), suggesting that an important functional correlation exists.…”
Section: Rem2 In Structural Plasticitymentioning
confidence: 99%